Evaluation of some Biochemical and Endocrine Profiles in transfusiondependent Iraqi major β - thalassemia patients - Majeed , Mohanad Salam (Iraqi Journal of Science, 2022)
Endocrine Abnormalities in β-thalassemia major are common disturbingcomplications, that need prompt management. Importance of this work was toevaluate the some biochemical parameters and endocrine hormones related tothe pubertal maturity and fertility status in cases with thalassemia. A sixty patients[38 males and 22 females] with β - thalassemia major against 30 healthy subjects[17 males and 13 females] were enrolle . The Blood levels of, Leptin, Vitamin D,thyroid function test, parathyroid hormone, ghrelin, and sex hormones weredetermined in the blood. Body Mass Index (BMI) was also evaluate. Resultsshowed that besides lower BMI, all hormones assessed were significantly lower inthalassemia β-major cases compared to healthy (p<0.001). Furthermore, the ghrelin/Leptin ratio in female cases was lower than the values obtained in the controls(p<0.001) .Finally, significant negative correlations, (p<0.05) were detectedbetween circulating levels of ghrelin and Follicle stimulating hormone ( FSH ),Luteinizing (LH) in male and female . The lower values of ghrelin and Leptin inthalassemia β-major possibly constitute another hormonal imbalance which maycntribute to the obstruction of growth and sexual maturation encountered inpatients group. Hypothyroidism occurs in proportion of β-major thalassemiapatients in the absence of clinical signs of hypothyroidism. Regular follow-up, forearly detection and timely treatment of such complications could improve, the typeof life of those patients.